Caracterización De La Conducta En Cautiverio De Las Guacamayas Verdes Colombianas (Ara Militaris) En El Zoológico De Santacruz En Bogotá (2023)
Behavior is essential to determine animal welfare in birds in captivity, therefore the importance of knowing and investigating how this specimen behaves in the wild, in order to make a comparison of its behavioral characteristics in captivity; It is important to bear in mind that if we talk about animal welfare, the proper functioning of the organism is included (which, among other things, things assume that animals are healthy), the emotional state of the animal (including the absence of negative emotions such as pain and fear) and the possibility of expressing some normal behaviors typical of the species (Fraser et al., 1997).